Exercise training in dilated cardiomyopathy improves rest and stress cardiac function without changes in cardiac high energy phosphate metabolism. Issue 14 (27th June 2012) - Holloway, Cameron J; Dass, Sairia; Suttie, Joseph J; Rider, Oliver J; Cox, Pete; Cochlin, Lowri E; Jackson, Hamish; Fast, Angela M; Johnson, Andrew W; Karamitsos, Theodoros D; Neubauer, Stefan; Clarke, Kieran
Abstract : Objective: To determine the effects of short-term exercise training on cardiac function and metabolism during rest and physical exercise in patients with heart failure from dilated cardiomyopathy (DCM). Design: Patients with DCM (n=15, age 58±2 years, NYHA class I–III) were studied before and after 8 weeks of cycle exercise for 20 min, five times per week. Main outcome measures: Cardiac volumes, function and high energy phosphate metabolism were measured using cardiac magnetic resonance during rest and 7 min of acute physical exercise (leg-raising). Results: At baseline, average left ventricular ejection fraction (LVEF) was 38±3%, which did not alter during 7 min of exercise. After 8 weeks of home exercise training, there was a 16% improvement in resting LVEF to 44±3% (p<0.01). Training caused a further 20% improvement in LVEF (p<0.05) during acute physical exercise. There was a negative correlation between subjects' baseline level of exercise and change in LVEF (r=−0.67, p<0.05), with sedentary patients having the greatest improvement. Cardiac phosphocreatine (PCr) to ATP ratio did not change during acute physical exercise or after exercise training. Conclusions: Short-term exercise training improves resting LVEF and LVEF with acute physical exercise with sedentary patients having the greatest improvement. There were no changes in cardiac PCr to ATP, before or after exercise training, suggesting that the improved cardiac function was not caused by improved energetics. Therefore, peripheral factors likely underlie the improved cardiac function in patients with heart failure after short-term exercise.